2013
DOI: 10.1021/jp407647f
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering on a Chemically Etched ZnSe Surface

Abstract: We report the observation of surface-enhanced Raman scattering (SERS) from a chemically etched ZnSe surface using 4-mercaptopyridine (4-MPy) as probe molecules. A thin film of ZnSe is grown by molecular beam epitaxy (MBE) and then etched using a strong acid. Protrusions of hemiellipsoidal nanoparticles are observed on the surface. Using the results of the Mie theory, we controlled the size of the nanoparticles to overlap significantly with maximum efficiency of near-field plasmon enhancement. In the Raman spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 25 publications
2
62
1
Order By: Relevance
“…From porous ZnO nanosheets, [15] TiO 2 photonic microarrays, [16] CuTe quantum dots, [17] chemically etched ZnSe, [18] and single Cu 2 O superstructure particles [19] to urchin-like W 18 O 49 , [20] MoO 3−x @MoO 3 nanosheets, [21] MoO 3−x quantum dots, [22] and oxygen-incorporating MoS x O y , [23] two types of methods are generally used to improve the SERS performance of semiconductor substrates: morphology design and element doping. As an increasing number of researchers are engaging in the study of semiconductor SERS substrates, research achievements regarding semiconductor SERS substrates have grown exponentially in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…From porous ZnO nanosheets, [15] TiO 2 photonic microarrays, [16] CuTe quantum dots, [17] chemically etched ZnSe, [18] and single Cu 2 O superstructure particles [19] to urchin-like W 18 O 49 , [20] MoO 3−x @MoO 3 nanosheets, [21] MoO 3−x quantum dots, [22] and oxygen-incorporating MoS x O y , [23] two types of methods are generally used to improve the SERS performance of semiconductor substrates: morphology design and element doping. As an increasing number of researchers are engaging in the study of semiconductor SERS substrates, research achievements regarding semiconductor SERS substrates have grown exponentially in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…2A shows the SERS spectrum of ADA at the 1 × 10 −4 M concentration mixed with Au@Ag NPs and the normal Raman spectrum of ADA solid powder. The differences between normal Raman and SERS spectra could be due to both the electromagnetic (i.e., localized surface plasmon resonance) and chemical (i.e., charge transfer) interactions between analytes and substrate surfaces [39]. It is well known, as conducting SERS experiment, some IR-active bands could be seen [40,41], such as the SERS band at 1028 cm −1 in this work.…”
Section: Portable Raman Detection Of Ada In Aqueous Solutionmentioning
confidence: 58%
“…In general, most LSPRs of semiconductors are observed in the long‐wavelength region due to a relatively lower electron density in the conduction band compared to metals. Thus the Raman enhancement of semiconductors is usually attributed to the chemical mechanism, and the enhancement factor is somewhat lower than those observed with noble metals . Recently, it was found that the free carrier concentrations can be tuned by doping and phase transitions, allowing engineering of LSPR frequencies to visible regions .…”
Section: Sers Detection On Noble‐metal‐free Substratesmentioning
confidence: 99%
“…[16] Since then, av ast variety of semiconductor materials such as Fe 3 O 4 , [17] a-Fe 2 O 3 , [18] Cu 2 O, [19] CuO, [20] Ag 2 O, [21] CdS, [22] ZnS, [23] CdTe, [24] TiO 2 , [10,25] PbS, [26] and AgS [27] were introduced and used as SERS-active substrates. Benefiting from the explosive development of nanoscience and nanotechnology,r ecent studies on TiO 2 , [28] CdTe, [29] Cu 2 O, [30] and ZnSe [31] have demonstrated large enhancement factors greater than 10 6 ,w hichi s comparable to the noble metal nanostructures.…”
Section: Semiconductor Substratesmentioning
confidence: 99%